Blockchain-enabled decentralized identity management: The case of self-sovereign identity in public transportation - Lukas Stockburger (Elsevier, 2021)
Identity management has been ripe for disruption over the past few years due to recurring incidents of data breaches that have led to personal information leaks and identity theft. The rise of blockchain technology has paved the way for the development of self-sovereign identity—a new class of user-controlled resilient identity management systems that are enabled by distributed ledger technology. This paper examines how SSI management can be used in a public transportation sector that spans different operators in multiple countries. Specifically, the paper explores how a blockchain-based decentralized identity management system can draw on the SSI framework to provide high-level security and transparency for all involved parties in public transportation ecosystems. Accordingly, building on analyses of the existing public transportation ticketing solutions, we elicited requirements of a comparable system based on the SSI principles. Next, we developed a low-fidelity prototype to showcase how passengers can utilize standardized travel credentials that are valid across different transportation networks in Europe. The proposed system eliminates the need for multiple travel cards (i.e., one for each transportation provider) and empowers individuals to have better control over the use of their identities while they utilize interoperable ticketing systems across Europe. Overall, building on the public transportation case, we offer a proof-of-concept that shows how individuals can better manage their identity credentials via the SSI framework.